Envolvimento dos sistemas serotoninérgico e opióide na ação do tipo antidepressiva do disseleneto de M-trifluormetilfenila em camundongos - Brüning, César Augusto (2012)
Serotonergic and opioid systems have been implicated in major depression and in the action mechanism of antidepressants. The organoselenium compound m-trifluoromethyldiphenyl diselenide (m CF3 PhSe)2 shows antioxidant and anxiolytic activities and is a selective inhibitor of monoamine oxidase A activity. The present study was designed to investigate the antidepressant-like effect of (m CF3 PhSe)2 in female mice, employing the forced swimming test. The involvement of the serotonergic and opioid systems in the antidepressant-like effect of (m CF3 PhSe)2 was appraised. (m CF3 PhSe)2 at doses of 50 and 100 mg/kg (p.o.) exhibited antidepressant-like action in the forced swimming test. The effect of (m CF3 PhSe)2 (50 mg/kg p.o.) was prevented by pretreatment of mice with WAY100635 (0.1mg/kg, s.c. a selective 5-HT1A receptor antagonist), ritanserin (4 mg/kg, i.p., a nonselective 5HT2A/2C receptor antagonist), ondansetron (1 mg/kg, i.p., a selective 5-HT3 receptor antagonist) and naloxone (1 mg/kg, i.p., a non-selective antagonist of opioid receptors). The administration of (m CF3 PhSe)2 and the interaction of antagonists with (m CF3 PhSe)2 did not cause any change in the locomotor activity assessed in the open-field test. These results suggest that (m CF3 PhSe)2 produced an antidepressant-like effect in the mouse forced swimming test and this effect seems most likely to be mediated through an interaction with serotonergic and opioid systems.